Governing mobile technology use for continuing professional development in the Australian nursing profession - Carey Ann Mather; Fred Gale; Elizabeth Anne Cummings (BMC, 2017)
Abstract Background The rapid growth in the use of mobile technology in Australia has outpaced its governance, especially in healthcare settings. Whilst some Australian professional bodies and organisations have developed standards and guidelines to direct appropriate use of social media and mobile technology, clear governance arrangements regarding when, where and how to use mobile technology at point of care in nursing are currently lacking. Discussion This paper analyses how the use of mobile technology by nurses at point of care is governed. It highlights the existence of a mobile technology paradox: an identified inability of nurses to access mobile technology in a context where it is increasingly recognised that its use in situ can enhance nursing practice while contributing to mobile learning and continuing professional development. While the recent release of the Registered Nurse Standards for Practice and accompanying Standard for Continuing Professional Development provides some direction regarding professional standards to support the use of mobile technology for mobile learning, we argue a more inclusive approach is required if emerging technologies are to be fully embraced. We describe how an implementation framework, underpinned by more detailed standards, guidelines and codes, could enable the nursing profession to be leaders in embedding mobile technology in healthcare environments nationally and globally. Conclusion The prevalence of mobile technology in Australia has outpaced its governance in healthcare environments. Its limited availability at point of care is hindering nursing practice, mobile learning and continuing professional development. We discuss the emergence of mobile technology and impediments for its use by nurses in situ. We analyse the professional codes governing nursing, outlining potential reforms to enable implementation of mobile technology at point of care by nurses.